2011
DOI: 10.1080/15435075.2010.550077
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Black Liquor Gasification Polygeneration System with CO2Capture in Pulp and Paper Mills to Produce Methanol and Electricity

Abstract: Based on KAM a pulp and paper mill, a polygeneration system integrated with a black liquor gasifier is proposed. The effects of CO 2 captured by oxygen-fuel combustion and Selexol absorption on the performance of the polygeneration system are studied in terms of both thermodynamic performance and cost assessment. Using the Aspen Plus simulator, the performance of the studied polygeneration systems are analyzed from the perspectives of the first and second laws of thermodynamics. Compared with the reference sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Importantly, the revenues from the pulp and newsprint sales are not represented in Figure 8 as these remained the same in all investigated cases. Though the cost of CO2 avoided is higher in the BLG-CaL cases (Case 3 and Case 4) than that in the CaL retrofit case (Case 2, 39.0 €/tCO2), it is still comparable to the results reported by Ferreira and Balestieri (2015) and Zhang et al (2011). Zhang et al (2011) presented the CO2 capture costs on the CO2 captured basis (26.3 and 40.9 €/tCO2 for oxy-fuel combustion and Selexol, respectively) that are lower than the cost per CO2 avoided.…”
Section: Economic Assessmentsupporting
confidence: 77%
See 1 more Smart Citation
“…Importantly, the revenues from the pulp and newsprint sales are not represented in Figure 8 as these remained the same in all investigated cases. Though the cost of CO2 avoided is higher in the BLG-CaL cases (Case 3 and Case 4) than that in the CaL retrofit case (Case 2, 39.0 €/tCO2), it is still comparable to the results reported by Ferreira and Balestieri (2015) and Zhang et al (2011). Zhang et al (2011) presented the CO2 capture costs on the CO2 captured basis (26.3 and 40.9 €/tCO2 for oxy-fuel combustion and Selexol, respectively) that are lower than the cost per CO2 avoided.…”
Section: Economic Assessmentsupporting
confidence: 77%
“…Though the cost of CO2 avoided is higher in the BLG-CaL cases (Case 3 and Case 4) than that in the CaL retrofit case (Case 2, 39.0 €/tCO2), it is still comparable to the results reported by Ferreira and Balestieri (2015) and Zhang et al (2011). Zhang et al (2011) presented the CO2 capture costs on the CO2 captured basis (26.3 and 40.9 €/tCO2 for oxy-fuel combustion and Selexol, respectively) that are lower than the cost per CO2 avoided. It should also be noted that figures reported in that study were estimated based on the capital costs reported in 2000 and 2005.…”
Section: Economic Assessmentsupporting
confidence: 77%
“…The experimental steps are as follows: (1) connect the experimental devices according to the experimental design and rise to the formation temperature; (2) put the core into the core holder and load the confining pressure and back pressure until reaching the experimental requirements; (3) saturated with the formation water, and make bound water by flooding experimental fluid, and stabilize the pressure; (4) open the experimental fluid accumulator and regulate the inlet pressure; (5) stabilize each pressure for 30 minutes according to the order from small to big, and record outlet fluid flow rate and its corresponding actual pressure; (6) measure three times repeatedly, and it is qualified when the flow rate error is less than 4% .…”
Section: Methodsmentioning
confidence: 99%
“…[2][3] In the process of low permeability reservoir development, the problems that the threshold pressure gradient is big and the water injection development is difficult which decide to take the development by the way of gas injection, especially the CO 2 injection development is an effective way of exploitation. [4][5] As an effective method of utilizing the greenhouse gas comprehensively, the technology of CO 2 flooding is taken increasingly to enhance the oil recovery. And the CO 2 miscible flooding technology also has a good application prospect in the low permeability reservoir development.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, greenhouse gases such as CO 2 have been increasing in the atmosphere, which induced global climate anomaly [ 1] . CO 2 flooding is considered one of the most promising methods for commercial application, which could not only improve our environment but enhance oil recovery [2,3] .…”
Section: Introductionmentioning
confidence: 99%